The Importance of Internal Control in Accounting Information Systems - Aulia, Dinda; Hazmi, Yusri; Isnani, Isnani; Khairunnisa, Meifiza (West Science Interdisciplinary Studies, 2024)
The objective of this article is to examine the significance of internal control in an accounting information system. An accounting information system serves as a framework for conducting accounting operations within an organization. A structured accounting information system is the result of the interaction between individuals, instruments, and methods. In the creation of financial reports, accounting information must be guaranteed to be free of errors and fraud, regardless of whether it was intentionally or inadvertently committed. This article employs a descriptive methodology, with library data serving as some of the data sources. The article's conclusion is that financial reports are a method of accountability from management to interested parties. Consequently, the reports that are generated must be of the highest quality and devoid of errors. Internal control is a manifestation of management's endeavor to achieve this objective by utilizing five control elements: control activities, control environment, risk assessment, information and communication, and supervision.